(3eRGejQ OGhO GdfHi Ydjg GdSdGes ((3KGhPhSj GdeYQha HGdeUdi s)
(3ChdgG (B:s
(3EdGg hGMO fHJOF HeYQaI Gddg hEQTGO fcJH eRGejQ eWQHI dOGhhO s
(3BNQgG (B:s
(3hXdGd GdehJ LdhSkG MJi jbhe CQLdfG Edi WQjb GdSdGeI fLRJ s
(3GdfSNI HgG MhGTs
(3fSNI KGdKIs
(3hgh hbajI Ydi cfjSI GdSjOI HWhQ SjfGA s
(3hbO Je fSNI SfI (B1767 (3b es
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdcJH GdSeGhjIs